Conservation and biodiversity in and around cocoa farms. Learning about sustainable cocoa production: a guide for participatory farmer training - Asare, R.; David, S.; Sonwa, D.J. (Forest & Landscape Denmark, 2009)
This manual on biodiversity and wildlife conservation in cocoa landscapes near protected areas aims at improving farmers’ knowledge on biodiversity and wildlife conservation in order to strengthen their decision making capacity. It helps farmers to understand the importance of biodiversity and wildlife conservation; understand their role as ecosystem managers; develop strategies for mitigating human-wildlife conflict; understand the national laws on biodiversity conservation and; develop an appreciation of the economic and conservation value of cocoa agroforests